Posterior Microphthalmia, Peripheral Pigmentary Retinal Changes, Yellow Lesions, and Cleft Lip: A Case Report and Literature Review - Nasser G. Alsaedi; Khalid Alrubaie (Case Reports in Ophthalmological Medicine)
Purpose. Posterior microphthalmia is a sporadic or inherited developmental ocular anomaly that may occur isolated or in association with multiple ocular and systemic anomalies. This report documents a case of posterior microphthalmia with atypical presentation including white dots in the posterior pole in addition to systemic anomalies including facial defect that can represent an underlying genetic mutation. Method. Case report. Results. A 29-year-old male with high hyperopia and history of bilateral clear lens presented with pigmentary changes and white-yellow dots in the posterior pole in both eyes. Patient had a history of cleft lip repair. A complete ocular evaluation including A/B scan and optical coherence tomography confirmed the diagnosis of posterior microphthalmia with a retinitis pigmentosa like fundus and drusen deposits in the subretinal pigment epithelium. Conclusion. The white-yellow drusenoid deposits in the posterior pole in association with posterior microphthalmia are poorly documented in the literature. Cases of craniofacial developmental defects in association with posterior microphthalmia may represent a genetic defect.